The Representation of Woman Acceptance Through Dimension of Character in Tim Burton's "Corpse Bride" - Ni Made Arnita Putri; I Wayan Juniartha (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
This study examines of how Corpse Bride representation of woman acceptance on Emily character through physiological, sociological and psychological dimension. The aim of this study is focusing on how the acceptance is reflected through the three dimensions aspect of Emily’s character in Corpse Bride movie. The data for this study was taken from Tim Burton’s movie Corpse Bride and was examined a descriptive qualitative method. The techniques utilized in this study included watching the movie, taking notes, selecting and classifying. This study presented in formal and informal method. The theoretical framework used in this study was the literary theory proposed by Wellek and Warren (1949). This study identified five data focusing on character of Emily, there are one physiological, two sociological and two psychological.